Interference between arsenic‐induced toxicity and hypoxia. (27th September 2018) - Kumar, Vijay; Vogelsang, Lara; Seidel, Thorsten; Schmidt, Romy; Weber, Michael; Reichelt, Michael; Meyer, Andreas; Clemens, Stephan; Sharma, Shanti S.; Dietz, Karl‐Josef
Abstract: Plants often face combinatorial stresses in their natural environment. Here, arsenic (As) toxicity was combined with hypoxia (Hpx) in the roots of Arabidopsis thaliana as it often occurs in nature. Arsenic inhibited growth of both roots and leaves, whereas root growth almost entirely ceased in Hpx. Growth efficiently resumed, and Hpx marker transcripts decreased upon reaeration. Compromised recovery from HpxAs treatment following reaeration indicated some persistent effects of combined stresses despite lower As accumulation. Root glutathione redox potential turned more oxidized in Hpx and most strongly in HpxAs. The more oxidizing root cell redox potential and the lowered glutathione amounts may be conducive to the growth arrest of plants exposed to HpxAs. The stresses elicited changes in elemental and transcriptomic composition. Thus, calcium, magnesium, and phosphorous amounts decreased in rosettes, but the strongest decline was seen for potassium. The reorganized potassium‐related transcriptome supports the conclusion that disturbed potassium homeostasis contributes to the growth phenotype. In a converse manner, photosynthesis‐related parameters were hardly affected, whereas accumulated carbohydrates under all stresses and anthocyanins under Hpx exclude carbohydrate limitation. The study demonstrates the existence of both synergistic since mutually aggravating effects and antagonistic effects of single and combined stresses. Abstract : The present study evaluates the physiological, biochemical, and transcriptomic changes induced by co‐occurrence of arsenic toxicity and hypoxia. The severe decline in nutrient contents especially K and S along with the perturbations in redox homeostasis leads to growth arrest as well as compromised recovery in combined stressed plants. The functional characterization of transcripts, which showed stress combination‐specific alterations, provides information on differences in signalling patterns between individual stresses and stress combination. The existence of both synergistic since aggravating effects and antagonistic changes of single and combined stresses is demonstrated.